THE DIRECTOR'S STRATEGY IN IMPROVING THE SERVICES OF EDUCATION AND SKILLS TRAINING PARTICIPANTS SAILERS ON POLITEKNIK PELAYARAN MALAHAYATI - Fazri Hermanto (JURNAL CURERE, 2022)
This research aims to find out: program formulation, management implementation, and the obstacles faced by the Director in carrying out management and improving the instructor's professionalism. This study uses a descriptive method with a qualitative approach—data collection techniques: observation, interviews, and documentation studies. The subjects of this research are directors, sub-sections, instructors, lecturers, and training participants. The study results show that: (1) Program Director in improving services to training participants, the mechanism of its formulation begins with finding out the cultural and social background, and deliberation between stakeholders such as sub-section heads, instructors, lecturers. The programs that are prepared are long-term, medium-term, and short-term programs, and all of these programs are guided by the regulations of the Ministry of Transportation and instructions from the IMO (International Maritime Organization). All of this is already in the management of the Director as stated in the Director's program to improve services. (2) The Director implements director management to improve service by the Director applying the management to himself as an example for his subordinates, and the Director takes approaches to improve the instructor's professionalism